2023
DOI: 10.21873/invivo.13225
|View full text |Cite
|
Sign up to set email alerts
|

Awake Breast Surgery: A Systematic Review

GIANLUCA VANNI,
GIACOMO COSTANZO,
MARCO PELLICCIARO
et al.

Abstract: Background/Aim: Awake surgery has become a valid alternative to general anesthesia in many surgery fields. This technique played a very important role during the COVID-19 period. The growing use of this technique has many advantages. We performed a systematic review to study the potentialities of awake breast surgery. Materials and Methods: We searched Pubmed, Embase, and Cochrane library database and retrieved a total of 109 records. Fortynine of them were excluded as unsuitable. Finally, we selected a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Shorter duration of hospital stay and reduced costs have been reported without influencing outcomes. Recent studies [15,16] have shown that awake breast surgery is associated with reduced surgical stress when compared to general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Shorter duration of hospital stay and reduced costs have been reported without influencing outcomes. Recent studies [15,16] have shown that awake breast surgery is associated with reduced surgical stress when compared to general anaesthesia.…”
Section: Discussionmentioning
confidence: 99%